Carbapenems to Treat Multidrug and Extensively Drug-Resistant Tuberculosis: A Systematic Review - Sotgiu, Giovanni; D’Ambrosio, Lia; Centis, Rosella; Tiberi, Simon; Esposito, Susanna; Dore, Simone; Spanevello, Antonio; Migliori, Giovanni (International journal of molecular sciences, 2016)
Background: Carbapenems (ertapenem, imipenem, meropenem) are used to treat multidrug-resistant (MDR-) and extensively drug-resistant tuberculosis (XDR-TB), even if the published evidence is limited, particularly when it is otherwise difficult to identify the recommended four active drugs to be included in the regimen. No systematic review to date has ever evaluated the efficacy, safety, and tolerability of carbapenems. Methods: A search of peer-reviewed, scientific evidence was carried out, aimed at evaluating the efficacy/effectiveness, safety, and tolerability of carbapenem-containing regimens in individuals with pulmonary/extra-pulmonary disease which was bacteriologically confirmed as M/XDR-TB. We used PubMed to identify relevant full-text, English manuscripts up to the 20 December 2015, excluding editorials and reviews. Results: Seven out of 160 studies satisfied the inclusion criteria: two on ertapenem, one on imipenem, and four on meropenem, all published between 2005 and 2016. Of seven studies, six were retrospective, four were performed in a single center, two enrolled children, two had a control group, and six reported a proportion of XDR-TB cases higher than 20%. Treatment success was higher than 57% in five studies with culture conversion rates between 60% and 94.8%. Conclusions: The safety and tolerability is very good, with the proportion of adverse events attributable to carbapenems below 15%.